Use of ionic liquids as media for the biocatalytic preparation of flavonoid derivatives with antioxidant potency - Katsoura, M. H.; Polydera, A. C.; Tsironis, L.; Tselepis, A. D.; Stamatis, H. (2006)
Biocatalytic preparation of acylated derivatives of flavonoid glycosides was performed using various immobilized lipases in two different ionic liquids, namely 1-butyl-3-methylimidazolium tetrafluoroborate ([bmim]BF4) and 1-butyl-3-methylimidazolium hexafluorophosphate ([bmim]PF6). The influence of various reaction parameters on the performance and the regioselectivity of the biocatalytic process was pointed out, using as model reaction the acylation of naringin and rutin with vinyl butyrate, catalyzed by immobilized Candida antarctica lipase at 60 degrees C. The biocatalytic modification of flavonoids strongly depended on the ionic liquid used, the molar ratio of substrates, as well as the acyl donor chain length. The highest conversion yield (about 65% after 96 h of incubation) was obtained with short chain acyl donors (up to four carbon atoms), at a relatively high molar ratio (10-15) in both ionic liquids used. The amount of monoacylated flavonoid derivatives produced in a single-step biocatalytic process in [bmim]BF4 was up to 5.5 g/L for monoacylated rutin and 30 g/L for monoacylated naringin. The regioselectivity of the process was higher in [bmim]BF4 than in [bmim]PF6 or organic solvents. Reaction rates observed in ionic liquids were up to four times higher than those reported for organic media. The acylation of sugar moiety of rutin with various acyl donors affected its antioxidant potential towards both isolated LDL and total serum model in vitro. A significant increase of antioxidant activity was observed for rutin-4"'-O-oleate. (c) 2006 Elsevier B.V. All rights reserved. Journal of Biotechnology